Demographics, practice patterns and long-term outcomes of patients with non–ST-segment elevation acute coronary syndrome in the past two decades: the CREDO-Kyoto Cohort-2 and Cohort-3. Issue 2 (22nd February 2021) - Takeji, Yasuaki; Shiomi, Hiroki; Morimoto, Takeshi; Yoshikawa, Yusuke; Taniguchi, Ryoji; Mutsumura-Nakano, Yukiko; Yamamoto, Ko; Yamaji, Kyohei; Tazaki, Junichi; Suwa, Satoru; Inoko, Moriaki; Takeda, Teruki; et al.
Abstract : Objectives: To evaluate patient characteristics and long-term outcomes in patients with non–ST-segment elevation acute coronary syndrome (NSTEACS) in the past two decades. Design: Multicenter retrospective study. Setting: The Coronary REvascularization Demonstrating Outcome Study in Kyoto (CREDO-Kyoto) percutaneous coronary intervention (PCI)/coronary artery bypass grafting (CABG) Registry Cohort-2 (2005–2007) and Cohort-3 (2011–2013). Participants: 3254 patients with NSTEACS who underwent first coronary revascularisation. Primary and secondary outcome measures: The primary outcome was all-cause death. The secondary outcomes were cardiovascular death, cardiac death, sudden cardiac death, non-cardiovascular death, non-cardiac death, myocardial infarction, definite stent thrombosis, stroke, hospitalisation for heart failure, major bleeding, any coronary revascularisation and target vessel revascularisation. Results: Patients in Cohort-3 were older and more often had heart failure at admission than those in Cohort-2. The prevalence of PCI, emergency procedure and guideline-directed medical therapy was higher in Cohort-3 than in Cohort-2. In patients who received PCI, the prevalence of transradial approach, drug-eluting stent use and intravascular ultrasound use was higher in Cohort-3 than in Cohort-2. There was no change in 3-year adjusted mortality risk from Cohort-2 to Cohort-3 (HR 1.00, 95% CI 0.83 to 1.22, p=0.97). Patients in Cohort-3 compared with those in Cohort-2 were associated with lower adjusted risks for stroke (HR 0.65, 95% CI 0.46 to 0.92, p=0.02) and any coronary revascularisation (HR 0.76, 95%CI 0.66 to 0.87, p<0.001), but with higher risk for major bleeding (HR 1.25, 95% CI 1.06 to 1.47, p=0.008). The unadjusted risk for definite stent thrombosis was lower in Cohort-3 than in Cohort 2 (HR 0.29, 95% CI 0.11 to 0.67, p=0.003). Conclusions: In the past two decades, we did not find improvement for mortality in patients with NSTEACS. We observed a reduction in the risks for definite stent thrombosis, stroke and any coronary revascularisation, but an increase in the risk for major bleeding.